Determination of Ibuprofen in Pharmaceutical Formulations Using Differential Pulse Polarography - Ahmed, Heba Y.; Dikran, Sarmad B.; Al-Ameri, Salam A. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
A reliable differential pulse polarographic (DPP) method has been developed and applied for the determination of ibuprofen IBU in dosage form with dropping mercury electrode (DME) versus Ag/AgCl. The best peak was found at cathodic peak of -1.18 V in phosphate buffer at pH=4 and 0.025M of KNO3 as supporting electrolyte. In order to obtaine the highest sensitivity, instrumental and experimental parameters were examined including the type and concentration of supporting electrolyte, pH of buffer solution, pulse amplitude and voltage step time. Diffusion current showed a direct linear relationship to ibuprofen concentration in the range of (5 â€“ 30) Î¼g. mL-1 (2.43Ã— 10-5 â€“ 1.45 Ã— 10-4 molÂ·Lâ€“1) with correlation coefficient r= 0.9999, detection limit (S/N = 3) =3.40 Î¼g. mL-1 (1.65 Ã— 10-5 molÂ·Lâ€“1) and the value of precision in terms of relative standard deviation  RSD%, ranged between 0.374-0.5176 %. The established DPP method offers an excellent analytical figure of merits as well as its successful applicability to examine two commercial drug forms (tablet and suspension) for the determination of ibuprofen.